Between Hijrah and Siyāsah: Transnational Islamic Movements, Contextual Islamic Law, and Democratic Governance in Post-Reform Indonesia - Syahrir Karim; Nur Utaminingsih; Ismah Tita Ruslin (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2026)
The Hijrah movement in post-reform Indonesia has emerged as one of the most significant yet understudied phenomena at the intersection of Islamic jurisprudence, transnational Islamic networks, and democratic governance. As a mass religious transformation movement involving millions of predominantly urban Muslim millennials, Hijrah communities have increasingly become vehicles for transnational ideological currents — including Salafism, Ikhwanul Muslimin networks, and Hizbut Tahrir — that carry political implications challenging Indonesia's pluralist democratic foundations. Despite its growing significance, existing scholarship has examined the Hijrah movement primarily through sociological or political science lenses, without systematically analyzing how Islamic legal traditions — particularly siyāsah shar'iyyah (Islamic political jurisprudence) and fiqh al-siyāsah (Islamic governance jurisprudence) — both shape and evaluate the political orientation of Hijrah communities. This study addresses that gap through a qualitative approach combining observation of offline and online Hijrah activities with systematic literature analysis, integrated with the theoretical frameworks of denationalization (Sassen), transnational Islam (Roy; Mandaville), and Islamism (Hadiz; Muhtadi), and enriched by the normative lens of contextual Islamic law. The findings establish three conclusions: first, the Hijrah movement operates as a locally-rooted expression of transnational Islamic ideological networks whose political implications range from democratic participation to exclusivist identity politics; second, the movement's ideological spectrum — spanning conservative Salafi, Islamist, and post-Islamist typologies — reflects competing interpretations of maṣlaḥah 'āmmah (public interest) and siyāsah shar'iyyah regarding the legitimate relationship between Islam and the modern state; and third, contextual Islamic law — particularly the maqāṣid al-sharī'ah principles of ḥifẓ al-nafs (preservation of life), ḥifẓ al-dīn (preservation of religion), and ḥifẓ al-'aql (preservation of reason/intellect) — provides normative Islamic grounds for evaluating which expressions of Hijrah political activism are compatible with democratic pluralism and which constitute threats to maṣlaḥah mursalah at the national level. This study contributes a contextual Islamic law framework for analyzing transnational Islamic movements, demonstrating that siyāsah shar'iyyah — not merely social movement theory — is an essential analytical lens for understanding the relationship between religious movements and democratic governance in Muslim-majority societies